Research on the Assessment of the Driving Effect of Digital Technological Innovation on the Income Increasing Efficiency Of Urban and Rural Residents in the Yellow River Basin - Liu, Mengling (International Journal of Computer Science and Information Technology, 2024)
The Yellow River Basin is a key region for the national regional coordinated development strategy and the construction of the Belt and Road. Promoting the income increase of urban and rural residents in various provinces of the Yellow River Basin is the key to cultivate new drivers of high-quality development and further promote common prosperity. Using the super-efficient DEA model, this paper analyzes the impact efficiency of digital technology innovation on the income increase of urban and rural residents in nine provinces (autonomous regions) of the Yellow River Basin from 2012 to 2022, and draws the following conclusions: (1) On the whole, the impact efficiency of digital technology innovation on the income increase of urban and rural residents in the Yellow River Basin has not reached the effective level. (2) There are regional differences in the impact efficiency of digital technology innovation on the income increase of urban and rural residents. Areas with superior geographical location, relatively high per capita income and large population can better promote the increase of urban and rural residents' income. (3) In terms of policies, it is necessary to focus on strengthening the infrastructure construction of the Yellow River Basin, further guide and support enterprises to carry out industrial upgrading and transformation, promote the application of digital technology in traditional industries, formulate specific policies and measures according to the characteristics and status quo of each region, comprehensively utilize the advantages of digital technology innovation, and then promote economic development and the improvement of resident income level.